Effectiveness of Advertising and Sales Promotion on Buying Decision of Smartphones in Kathmandu Valley - Adhikari, Nisha Sharma (Journal of Business and Social Sciences Research, 2018)
Advertising has the most prominent and vital impact on buying behavior of consumers. Smart phones have gained a lot of popularity in Nepal and are considered to be a great multimedia tool. With such growing demand of smartphones, the need for effective advertising has also been raised. This paper centers on the impact of advertising on the sales volume of Smartphones. This work will shed light on how advertising can really affect a consumer’s buying decisions in a growing economy and how successful advertising can keep businesses going even in the midst of a tough competition. The entire data is collected by distributing structured questionnaire to the 150 respondents within Kathmandu valley. The outcome generated from descriptive statistic is that, most of the respondents own Samsung phone followed by iPhone and Online media is considered as the most effective adverting tool among other two. From the findings, we can also examine that there is insignificant relationship between gender and trust of information towards advertisement. Similarly, online, offline and electronic media have a insignificant association between gender, whereas influence through the advertisement of a brand has a significant association among age. Further the correlation analysis shows that there is a significant association among online, offline and electronic media.  Journal of Business and Social Sciences Research, Vol. 1, No. 2, pp. 169-184